2012
DOI: 10.1016/j.econlet.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

How regulation affects network and service quality in related markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…With an unregulated internet, we consider that the ISP's investment is determined by the complementarity between content and internet service and the ability to extend monopoly power beyond the internet market. The former e¤ect has been extensively studied in Haucap and Klein (2012), Broos and Gautier (2017), and Baranes and Vuong (2019) 8 who have considered that a higher content value leads to higher internet demand and vice versa 9 . To account for the latter e¤ect, such as in Carroni et al (2018) and Montes et al (2019), we follow the contractual framework initiated by Jehiel and Moldovanu (2000) to explore the ISP's market position to extract rents through lumpsum payments: The ISP could vary the quality upgrades; hence, it could capture all the CPs'marginal pro…ts through a take-it-or-leave-it o¤er.…”
Section: Introductionmentioning
confidence: 99%
“…With an unregulated internet, we consider that the ISP's investment is determined by the complementarity between content and internet service and the ability to extend monopoly power beyond the internet market. The former e¤ect has been extensively studied in Haucap and Klein (2012), Broos and Gautier (2017), and Baranes and Vuong (2019) 8 who have considered that a higher content value leads to higher internet demand and vice versa 9 . To account for the latter e¤ect, such as in Carroni et al (2018) and Montes et al (2019), we follow the contractual framework initiated by Jehiel and Moldovanu (2000) to explore the ISP's market position to extract rents through lumpsum payments: The ISP could vary the quality upgrades; hence, it could capture all the CPs'marginal pro…ts through a take-it-or-leave-it o¤er.…”
Section: Introductionmentioning
confidence: 99%
“…Haucap and Klein () consider investment incentives in a similar market, where an upstream monopoly network provides services to a downstream duopoly. They focus on investments in service quality, and assume the network access charge is exogenously regulated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Polykalas and Prezarakos (2015) verified that the Common Regulatory Framework for Electronic Communications promotes competition in the EU. In a theoretical and insightful work, Haucap and Klein (2012) proved that network regulation negatively affects investment incentives in the network market; however, the effects on investment in complementary services can be either negative or positive depending on the weight assigned by consumers to infrastructure vs service quality. Regarding the type of regulation, Glass et al (2013) found evidence for the USA of financial distress faced by the Rural Local Exchange Carriers when passing from the rate-of-return regulation to a price cap regulation.…”
Section: Introductionmentioning
confidence: 99%